(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Anefficient capital market is a prerequisite of economic development. Broadly,capital market can be classified into new issue market (primary market) andsecondary market (stock market). The new issue market deals with new securities,which were not previously traded, and secondary market is mainly concerned withthe trading of securities previously issued. Resource allocation in the capitalmarket is facilitated by the effective support of financial intermediaries thatinclude various stock exchanges, issue houses, underwriting agencies andmerchant banks.